Ancestralidad Indígena: desvelando la vida, muerte y renacimiento de los pueblos de la Sierra Nevada de Santa Marta, Colombia - Perilla León, Viviana Marcela (2023)
The literature related to palliative care and indigenous populations generally reports the experiences of first peoples from the northern hemisphere, addressing topics such as dying outside their lands, traditional care, ceremonies, and rituals after death. This material does not always focus on occupations that refer to the affirmation of life or the preparation for death in indigenous communities in Latin America, especially in Colombia. Thus, this study aims to describe the occupational processes at the end of life of Colombian indigenous communities in the Sierra Nevada de Santa Marta. It seeks to reveal the appreciation of non-Eurocentric palliative care, in the construction of individual and collective meanings of the Kankuamo and Arhuaco peoples around the processes of death, dying and mourning. Under a decolonial positionality, community contemplation, alternative conversation and configurative reflection are integrated as guiding actions that accompany native science, using Tejido/Yarning, as a resource based on respect, freedom, reciprocity, specificity, inclusion and cultural safety. Through seven purposes: therapeutic, social, family, intercultural, investigative, collaborative and relational, feelings were woven with the Mayoras, spiritual authorities (Mamus, Akumama), bereaved families and indigenous children. Themes related to care in the face of the processes of death were intertwined; the cosmological origin of death and its payments; postmortem ancestral ceremonies such as "seeding" and "eysa/mortuoria"; the reframing of pain in the face of loss; ways of intercultural learning about death and dying; as well as Mother Earth, spirituality and religion, reflecting on the meanings of their collective, ancestral and traditional memories toward the end of life. Thus, the study can be a contribution to history and intercultural dialogues, to broaden the understanding of health professionals, notably occupational therapists, about the culturally safe occupational dimension of death, dying and mourning based on the feelings and actions of indigenous communities.